Post-Holocaust : interpretation, misinterpretation, and the claims of history - Lang, Berel (Bloomington : Indiana University Press, 2005)
A philosopher addresses conceptual and ethical questions that arise from historical accounts of the Holocaust.
Cover; Contents; Acknowledgments; Introduction; One: The Nazi as Criminal; Two: Forgiveness, Revenge, and the Limits of Holocaust Justice; Three: Evil, Suffering, and the Holocaust; Four: Comparative Evil:Measuring Numbers, Degrees, People; Five: The Grammar of Antisemitism; Six: The Unspeakable vs. the Testimonial: Holocaust Trauma in Holocaust History; Seven: Undoing Certain Mischievous Questions about the Holocaust; Eight: From the Particular to the Universal, and Forward; Nine: Oskar Rosenfeld and Historiographic Realism (in Sex, Shit, and Status)Ten: Lachrymose without Tears: Misreading the Holocaust in American LifeEleven: "Not Enough" vs. "Plenty" / Which Did Pius XII?; Twelve: The Evil in Genocide; Thirteen: Misinterpretation as the Author's Responsibility (Nietzsche's Fascism, for Instance); Afterword: Philosophy and/of the Holocaust; Notes; Index.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
In English.
Keywords: Holocaust, Jewish (1939-1945) -- Historiography; Holocaust, Jewish (1939-1945) -- Influence; Holocaust, Jewish (1939-1945) -- Moral and ethical aspects; Antisemitism -- History; Holocauste, 1939-1945 -- Historiographie; Holocauste, 1939-1945 -- Influence; Holocauste, 1939-1945 -- Aspect moral; Antisémitisme -- Histoire; HISTORY -- Holocaust; Antisemitism; Ethics; Historiography; Influence (Literary, artistic, etc.); Rezeption; Judenvernichtung; Geschichtsschreibung; 1939-1945; FACarts -- Jewish studies -- History; ER -- Internet -- Book -- Full text; Electronic books; History; Electronic book